Issues and Challenges in Implementing the SDGs in Nepal - Prasai, Dilli R. (BARUN Journal, 2025)
The Government of Nepal has adopted various policies and programs to accelerate the implementation of Sustainable Development Goals in Nepal and had put in place the institutional and financial arrangements. The National Planning Commission (NPC) is the principal agency for SDG monitoring and has taken a number of initiatives towards attaining the SDGs by engaging relevant stakeholders in this process. Nepal is one of the first country to take stock of its status on the proposed Sustainable Development Goals in 2016, followed by preparing SDGs status and roadmap 2016-2030 and SDGs Needs Assessment, Costing and financing Strategy